Langerhans cell sarcoma with an aberrant cytoplasmic CD3 expression - Xu, Zhaodong; Padmore, Ruth; Faught, Carolyn; Duffet, Lisa; Burns, Bruce F (Université d'Ottawa | University of Ottawa, 2012)
Abstract Langerhans cell sarcoma is a rare and aggressive high grade hematopoietic neoplasm with a dismal prognosis. It has a unique morphological and immunotypic profile with a CD1a/ langerin/S100 + phenotype. T cell lineage markers except for CD4 in Langerhans cell sarcoma have not been documented previously. We report a case of 86 year-old male of Caucasian descent who presented with an enlarging right neck mass over 2 months with an underlying unknown cause of anemia. Computed tomography scan of the neck, chest and abdomen revealed generalized lymphadenopathy and mild splenomegaly suspicious for lymphoma. Diagnostic core biopsy performed on right neck mass revealed a possible T cell lymphoma with expression of T cell lineage specific marker CD3 but conclusive diagnosis could not be made due to insufficient core biopsy sample. Further excisional biopsy performed on a left inguinal node showed a hematopoietic neoplasm with features of Langerhans cell sarcoma with a focal cytoplasmic CD3 expression in 30-40% of the tumor cells. PCR for T cell receptor (TCR) gene rearrangement failed to demonstrate a clonal gene rearrangement in the tumor cells arguing against a T cell lineage transdifferentiation, suggesting an aberrant CD3 expression. To the best of our knowledge, this case represents the first report of Langerhans cell sarcoma with an aberrant cytoplasmic CD3 expression. Virtual slides http://www.diagnosticpathology.diagnomx.eu/vs/2065486371761991